Theoretical and Experimental DNA Computation - Amos, Martyn (Springer, 2005)
This book provides a broad overview of the entire field of DNA computation, tracing its history and development. It contains detailed descriptions of all major theoretical models and experimental results to date, which are lacking in existing texts, and discusses potential future developments. It also provides a useful reference source for researchers and students, and an accessible introduction for people new to the field. The field of DNA computation has flourished since the publication of Adleman's seminal article, in which he demonstrated for the first time how a computation may be performe.